Contibuições para o estudo da modelagem de aerogeradores baseados no gerador de indução duplamente alimentado - Schmidlin Júnior, Celso Rogério (2017)
The wind energy conversion system based on the doubly-fed induction generator is very susceptible to sags and imbalances in the grid voltages, since the stator of this machine is directly connected to the electric grid. Thus, to increase the low voltage ride-through and to improve the performance of the generator during unbalanced grid voltages, many studies have proposed that the control system also act on the negative sequence components, since the voltage unbalance and most of the sags give rise to these components. Thus, are further increased the complexity, computational effort and simulation time of this complex system. This creates room for the use of reduced-order models that, although less precise, reduce computational efforts and simulation time, in addition to making the system behavior analysis simpler. In this context, it is proposed in the present thesis a simplified model for the positive and negative sequences of the wind energy conversion system based on the doubly-fed induction generator. For the validation of the proposed model, its results are compared with those coming from large-scale simulations, which use high-order models. Comparisons are also made with the results from an experimental reduced power prototype. Both in the simulations and in the experimental tests, proportionalintegral controllers are used to control the positive sequence components of the rotor currents and proportional+resonant to the respective negative sequence components. Although this technique is already consolidated, it is presented the equation of the feed-forward terms, so that the direct and quadrature axis components become decoupled. For the experimental implementation, it is proposed in this thesis a simplified model for the doubly-fed induction generator with open stator during the synchronization process. To obtain such model, all the electrical losses of the machine in this situation are considered as grouped in the rotor resistance. In addition, it is detailed a simplified estimation method of the machine parameters. Thus, it is intended to make the current controllers tuning simpler, more precise and less susceptible to loss of tuning (due to the non-consideration of magnetic losses and other less important ones) during the synchronization of the generator with the electric grid.